Hallermann-Streiff syndrome: Case report with abnormal pulp calcifications - Nour Ammar; Magda M. El-Tekeya (Frontiers Media S.A., 2022)
Hallermann-Streiff syndrome (HSS) is a disorder of rare occurrence affecting the craniofacial complex, with approximately 200 cases reported in the literature. Nonetheless, its distinctive facial features render it highly recognizable. We present the case of a 5-year-old girl with this syndrome and review the dental manifestations and management in this patient. In addition to the diagnostic facial features of brachycephaly with frontal bossing, beak-shaped nose, microphthalmia, and mandibular retrusion, multiple dental manifestations were noted, including the absence of the mandibular condyle, ghost teeth, and unusual pulpal calcifications in both the primary and the permanent teeth, which have not been previously reported in a case of HSS. There is no consensus on the suitable treatment plan to be given for HSS patients at a young age due to an underreporting of these cases in the literature. In this report, we discuss pediatric dental management options for a patient with HSS and share her perspective on the treatment.